Instructional Framework for Emergency Remote Teaching in Higher Education - Anna Rubtsova; Natalia Semenova; Nora Kats; Olga Zheleznyakova (Education Sciences, 2023)
The COVID-19 crisis has considerably changed the educational landscape and resulted in a scientific debate on the efficacy and prospects of online education. Recent research is focused on analyzing the psychological and instructional difficulties faced by both educators and learners during emergency remote teaching (ERT). However, a limited number of studies tends to present a holistic instructional framework that could benefit educators in situations of a similar educational crisis. This study aims at identifying psychological and pedagogical implications for instructional framework design in situations of abrupt transition to online learning. Employing a qualitative approach, this study is based on the dataset collected from 152 students obtaining bachelor’s and master’s degrees in social sciences. This dataset was analyzed and interpreted by means of descriptive statistics. The findings helped to identify students’ perceptions of ERT, core difficulties, and preferences which underlay the conceptualization of the instructional framework adjustable for ERT. The presented instructional considerations could contribute to the effective design of technology-assisted courses in the context of higher education.